Diversity of ground beetles (Coleoptera: Carabidae) in oil palm plantation in endau-rompin, Pahang, Malaysia - Zaki N.-I.A.; Nasir D.M.; Aziz A.; Azhari L.-H.; Saputra A.; Halim M.; Muslim S.A.; Abdullah N.-A.; Asri L.-N.; Faszly Rahim (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by SCOPUS